The psychometric properties of the Persian version of the innovation support inventory (ISI-12) in clinical nurses: a methodological cross-sectional study - Azam Hashemian Moghadam; Reza Nemati-Vakilabad; Reza Imashi; Roghayeh Yaghoobi Saghezchi; Pouya Dolat Abadi; Mobina Jamshidinia; Alireza Mirzaei (BMC, 2024)
Abstract Background Innovation in nursing involves applying new knowledge to create novel ideas, methods, or technologies, resulting in higher-quality care and improved patient outcomes. Adequate support for innovation is crucial for progress in nursing. This study aimed to translate the Innovation Support Inventory (ISI-12) into Persian and assess its psychometric properties specifically among clinical nurses. Methods A methodological cross-sectional study was conducted from September 2022 to July 2023 to evaluate the face, content, and construct validity of the ISI-12. Construct validity was assessed through confirmatory factor analysis (CFA) and convergent and discriminant validity evaluation using data obtained from 321 clinical nurses. The test-retest stability and internal consistency of the ISI-12 were also evaluated to assess its reliability. Results The Persian version of the ISI-12 validation through confirmatory factor analysis has confirmed its fit with the proposed three-factor model. The ISI-12 demonstrated high reliability, as evidenced by a Cronbach's alpha coefficient (α = 0.969), McDonald's omega coefficient (ω = 0.922), coefficient H (H = 0.979), and mean inter-item correlation (ρ = 0.418). Additionally, the stability of the ISI-12 during two weeks among 40 clinical nurses was found to be excellent, with an ICC of 0.951. Conclusion The Persian version of the ISI-12 is a valid inventory for evaluating the innovation Support of clinical nurses.